2010
DOI: 10.1021/es101971m
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cultures Preferentially Removing Singly Flanked Chlorine Substituents from Chlorobenzenes

Abstract: The wide though not ubiquitous distribution of chlorobenzene-dechlorinating bacteria in anaerobic sludge from German sewage plants is demonstrated. The model substrates 1,2,3- and 1,2,4-trichlorobenzene (TCB) were dechlorinated to dichlorobenzenes (DCBs) and monochlorobenzene (MCB) via distinct pathways. For easy visualization and differentiation of the pathways, a novel plotting method was developed. While many of the cultures showed a dechlorination pattern similar to that previously found for Dehalococcoide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…1,3,5-TCB is the product of dehalogenation of HCB or QCB by organisms with a preference for doubly flanked chlorines, and has been detected as an end-product in several mixed cultures ,, and pure cultures containing Dehalococcoides spp. and relatives. ,, Dehalogenation of 1,3,5-TCB to 1,3-DCB and MCB has been observed before in mixed communities, but a causative organism has not been identified. Dehalobacter sp.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…1,3,5-TCB is the product of dehalogenation of HCB or QCB by organisms with a preference for doubly flanked chlorines, and has been detected as an end-product in several mixed cultures ,, and pure cultures containing Dehalococcoides spp. and relatives. ,, Dehalogenation of 1,3,5-TCB to 1,3-DCB and MCB has been observed before in mixed communities, but a causative organism has not been identified. Dehalobacter sp.…”
Section: Discussionmentioning
confidence: 90%
“…strain 13DCB1 dehalogenated 1,3,5-TCB to MCB with little detectable buildup of 1,3-DCB, consistent with its ability to use meta-substituted chlorines, and qPCR studies indicated this dehalogenation supported its growth (Figure B). This pattern for 1,3,5-TCB utilization is different from that described for an enrichment culture in which there was significant buildup of 1,3-DCB and no MCB. More recently, enrichments from Vietnam sediments were shown to dechlorinate 1,3,5-TCB to MCB, but 1,3-DCB accumulated as an intermediate, suggesting mechanistic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been carried out with Dehalococcoides strains on the transformation of simply structured organohalides such as chlorinated benzenes, , phenols, ethenes, ethanes, and propanes, among others. Dehalococcoides strains were also able to dehalogenate di- and tricyclic aromatic compounds such as polychlorinated biphenyls, chlorinated dioxins, or brominated diphenyl ethers .…”
Section: Introductionmentioning
confidence: 99%
“…15−18 Reductive dehalogenase homologous genes (rdh genes) are particularly abundant in Dehalococcoides species with 10−36 copies in the known D. mccartyi genomes. 19 Many studies have been carried out with Dehalococcoides strains on the transformation of simply structured organohalides such as chlorinated benzenes, 20,21 phenols, 22 ethenes, 23−25 ethanes, 26 and propanes, 27 among others. Dehalococcoides strains were also able to dehalogenate di-and tricyclic aromatic compounds such as polychlorinated biphenyls, 28−30 chlorinated dioxins, 31−33 or brominated diphenyl ethers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…D. mccartyi strain CBDB1 [6] was shown to reductively dehalogenate an exceptionally broad spectrum of halogenated, mostly aromatic, electron acceptors ranging from polychlorinated to -brominated benzenes (e.g., [7,8], polychlorinated dibenzo-p-dioxins [9], biphenyls [10], phenols [11], including bromophenol blue [12], and the herbicide 2,4,5-T [13]). Despite its slow growth, with doubling times between 1 and 3 days [14], D. mccartyi is a key organism for the bioremediation of groundwater and soil contaminated with organohalides [15].…”
Section: Introductionmentioning
confidence: 99%